Acesso a saúde reprodutiva enquanto direito: um estudo a partir do planejamento reprodutivo - Marques, Daniela Ferreira Bastos (2024)
Sexual and reproductive rights are fundamental to ensuring equality and human dignity, requiring public policies that promote reproductive health. Primary Health Care (PHC) plays a crucial role in this context and serves as a privileged access point to reproductive health. Including information on sexual and reproductive health in PHC allows women to make informed choices, care for themselves and others, prevent risky situations, promote health, and gain a holistic view of body and mind. This study aims to analyze access to reproductive health in the municipality of Camaçari-BA as a right through the lens of reproductive planning, using the following access dimensions: political, socio-economic, organizational, technical, and symbolic. This is a qualitative exploratory study. Qualitative research is suitable for this study as it allows for the exploration of complex and subjective aspects, enabling an understanding of beliefs, values, and practices related to reproductive health. It also allows participants to express their experiences, fears, hopes, and challenges, which can aid in investigating issues related to health service accessibility, professional work, and reproductive rights. The study was conducted at Family Health Units (FHU) and Basic Health Units (BHU) in the CostaDistrict of Camaçari, with interview participants including women in reproductive planning, nurses, doctors, and municipal health managers involved in women’s health in Camaçari-BA.Data collection techniques included semi-structured interviews, document analysis, and systematic observation. Data were analyzed using thematic content analysis, with an Excel spreadsheet created to extract themes, leading to the identification of five categories. The research findings indicate a lack of awareness regarding the right to reproductive health in thepolitical dimension, highlighting barriers that limit access. In the socio-economic dimension,economic and social barriers hinder full access. In the organizational dimension, geographic access issues and structural weaknesses in services were found, with insufficient resources to ensure continuous and quality care. In the technical dimension, the lack of effective planning, fragile connections, and reception between users and services compromise continuity of care. The symbolic dimension revealed the influence of taboos, religious dilemmas, and misinformation about contraceptive methods, negatively impacting women’s autonomy and right to reproductive planning. The study observed a need to implement strategies such as welldefined and disseminated organizational flows, health education, and continuous training to improve access to reproductive health in Camaçari. As products of this study, two technical products were suggested, which were the creation of a section on the city hall website with documents on reproductive health and the development of a unified flowchart that maps all the assistance options for promoting reproductive health in the city's Health Care Network (RAS), and the scientific product, which was the manuscript.